Occupational stress and incidence of sick leave in the Belgian workforce: the Belstress study. Issue 6 (13th May 2004) - Moreau, M; Valente, F; Mak, R; Pelfrene, E; de Smet, P; De Backer, G; Kornitzer, M
Abstract : Context: Sick leave is a major problem in public health. The Karasek demands/control/social support/strain (JDCS) model has been largely used to predict a wide range of health outcomes and to a lesser extent sickness absence. Study objective: The aim of the study was to test the predictive power of the JDCS model in relation with one year incidence of sick leave in a large cohort of workers. Design and setting: Cohort study conducted between 1994 and 1998 in 25 companies across Belgium. Participants: A total of 20 463 workers aged 35 to 59 years were followed up for sick leave during one year after the baseline survey. Outcomes: The outcomes were a high sick leave incidence, short spells (⩾7 days), long spells (⩾28 days), and repetitive spells of sickness absence (⩾3 spells/year). Main results: Independently from baseline confounding variables, a significant association between high strained jobs with low social support and repetitive spells of sickness absence was observed in both sexes with odds ratios of 1.32 (99% CI, 1.04 to 1.68) in men and 1.61 (99% CI, 1.13 to 2.33) in women. In men, high strained jobs with low social support was also significantly associated with high sick leave incidence, and short spells of sick leave with odds ratios of 1.38 (99% CI, 1.16 to 1.64) and 1.22 (99% CI, 1.05 to 1.44) respectively. Conclusions: Perceived high strain at work especially combined with low social support is predictive of sick leave in both sexes of a large cohort of the Belgian workforce.